MRI study of the size, symmetry and function of the trunk muscles among elite cricketers with and without low back pain. Issue 10 (7th December 2007) - Hides, J; Stanton, W; Freke, M; Wilson, S; McMahon, S; Richardson, C
Abstract : Objectives: To determine if asymmetry of trunk muscles and deficits of motor control exist among elite cricketers with and without low back pain (LBP). Design: Single-blinded observational quasi-experimental design study Setting: Assessments were conducted in a hospital setting. Participants: Among a total eligible sample of 26 male elite cricketers (mean age 21.2 (SD 2.0) years), selected to attend a national training camp, 21 participated in the study. Risk factors: The independent variables were 'group' (LBP or asymptomatic) and 'cricket position' (fast bowler versus the rest of the squad). Main outcome measurements: The dependent variables were the cross-sectional areas (CSA) of the quadratus lumborum (QL), lumbar erector spinae plus multifidus (LES + M) and psoas muscles, the thickness of the internal oblique (IO) and transversus abdominis (TrA) muscles, and the amount of lateral slide of the anterior abdominal fascia. Results: The QL and LES + M muscles were larger ipsilateral to the dominant arm. In the subgroup of fast bowlers with LBP, the asymmetry in the QL muscle was the greatest. The IO muscle was larger on the side contralateral to the dominant arm. No difference between sides was found for the psoas and TrA muscles. Cricketers with LBP showed a reduced ability to draw in the abdominal wall and contract the TrA muscle independently of the other abdominal muscles. Conclusions: This study provides new insights into trunk muscle size and function in elite cricketers, and evidence of impaired motor control in elite cricketers with LBP. Rehabilitation using a motor control approach has been shown to be effective for subjects with LBP, and this may also benefit elite cricketers.